Some remarks concerning Riemannian extensions - Aslanci, S.; Kazimova, S.; Salimov, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We study some properties of Riemannian extensions in cotangent bundles with the help of adapted frames.